Prevalence, content and significance of advance care planning in nursing home patients. (2nd January 2022) - Kastbom, Lisa; Falk, Magnus; Karlsson, Marit; Tengblad, Anders; Milberg, Anna
Abstract: Objective: Studies on advance care planning in nursing homes are rare, and despite their demonstrated favourable effects on end-of-life care, advance care plans are often lacking. Therefore, we wished to explore: (i) the prevalence of advance care plans in a Swedish nursing home setting using two different definitions, (ii) the content of advance care plans, (iii) adherence to the content of care plans and (iv) possible associations between the presence of advance care planning and background characteristics, physician attendance and end-of-life care. Design: Retrospective chart review. Setting: Twenty-two nursing homes in Sweden. Subjects: A total of 367 deceased patients (included between 1 June 2018 and 23 May 2020) who had lived in nursing homes. Main outcome measures: Electronic health record data on the prevalence of advance care plans with two different definitions and variables regarding background characteristics, physician attendance and end-of-life care, were collected. Results: Of the study population, 97% had a limited care plan (ACP I) documented. When using the comprehensive definition (ACP II), also including patient's preferences and involvement of family members in advance care planning, the prevalence was 77%. Patients with dementia more often had care plans, and a higher physician attendance was associated with presence of advance care plans. Prescription of palliative drugs and information to family members of the patient's deterioration and impending death were more common in patients with care plans compared to those where such plans were missing. There was adherence to the care plan content. Conclusion: In contrast to previous research, this study showed a high prevalence of advance care plans in nursing home patients. Patients with care plans more frequently received prescriptions of palliative drugs and their family members were informed to a greater extent about the patient's deterioration and impending death compared to those without care plans. These aspects are often seen as vital components of good palliative care. Key points: Studies on advance care planning in nursing homes are rare, and despite their demonstrated positive effects on end-of-life care, advance care plans are often lacking. The present study revealed a high prevalence of advance care plans (77-97% depending on definition) in nursing home patients. Patients with dementia more often had advance care plans, and a higher physician attendance was associated with presence of care plans. Advance care plans were positively associated with components of good palliative care, such as prescriptions of palliative drugs and information to family.